2004
DOI: 10.1063/1.1738211
|View full text |Cite
|
Sign up to set email alerts
|

The influence of groundwater chemistry on arsenic concentrations and speciation in a quartz sand and gravel aquifer

Abstract: We examined the chemical reactions influencing dissolved concentrations, speciation, and transport of naturally occurring arsenic ͑As͒ in a shallow, sand and gravel aquifer with distinct geochemical zones resulting from land disposal of dilute sewage effluent. The principal geochemical zones were: ͑1͒ the uncontaminated zone above the sewage plume ͓350 M dissolved oxygen ͑DO͒, pH 5.9͔; ͑2͒ the suboxic zone ͑5 M DO, pH 6.2, elevated concentrations of sewage-derived phosphate and nitrate͒; and ͑3͒ the anoxic zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 40 publications
0
37
1
1
Order By: Relevance
“…Mobilization of As into the groundwater of shallow alluvial aquifers in the Bengal Basin through natural processes involving reductive dissolution of Fe(III)-oxyhydroxide is widely accepted as the principal mechanism (Bhattacharya et al 1997(Bhattacharya et al , 2002a(Bhattacharya et al , b, 2006Nickson et al 1998Nickson et al , 2000BGS and DPHE 2001;Smedley and Kinniburgh 2002;Dowling et al 2002;Anawar et al 2003;Ahmed et al 2004;Horneman et al 2004;McArthur et al 2004). Solid phases, such as Mn/Al-oxyhydroxides as well as phyllosilicates, are also known to play an important role in the As cycling in the aquifers (Breit et al 2001;Kent and Fox 2004;Saunders et al 2005;Chakraborty et al 2007von Brömssen et al 2008). Mobilization of As due to oxidation of pyrite (Chowdhury et al 1999) and widespread application of phosphate fertilizer (Acharyya et al 2000) is not consistent with the geochemical evidence revealed by several studies (Nickson et al 2000;BGS and DPHE 2001;2002aHarvey et al 2002;Zheng et al 2004Zheng et al , 2005Swartz et al 2004;Horneman et al 2004;Ahmed et al 2004;Hasan et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mobilization of As into the groundwater of shallow alluvial aquifers in the Bengal Basin through natural processes involving reductive dissolution of Fe(III)-oxyhydroxide is widely accepted as the principal mechanism (Bhattacharya et al 1997(Bhattacharya et al , 2002a(Bhattacharya et al , b, 2006Nickson et al 1998Nickson et al , 2000BGS and DPHE 2001;Smedley and Kinniburgh 2002;Dowling et al 2002;Anawar et al 2003;Ahmed et al 2004;Horneman et al 2004;McArthur et al 2004). Solid phases, such as Mn/Al-oxyhydroxides as well as phyllosilicates, are also known to play an important role in the As cycling in the aquifers (Breit et al 2001;Kent and Fox 2004;Saunders et al 2005;Chakraborty et al 2007von Brömssen et al 2008). Mobilization of As due to oxidation of pyrite (Chowdhury et al 1999) and widespread application of phosphate fertilizer (Acharyya et al 2000) is not consistent with the geochemical evidence revealed by several studies (Nickson et al 2000;BGS and DPHE 2001;2002aHarvey et al 2002;Zheng et al 2004Zheng et al , 2005Swartz et al 2004;Horneman et al 2004;Ahmed et al 2004;Hasan et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In oxic environments, release of sediment-bound arsenic has been observed in response to elevated concentrations of phosphate (Kent and Fox, 2004) and oxidation of sulfide minerals at low pH values (McCreadie et al, 2000;Schreiber et al, 2000). In anoxic environments, sediment-bound arsenic can be mobilized by reductive dissolution or transformation of Fe(III) hydroxide coatings and reduction of arsenate (As(V)) to arsenite (As(III)) (e.g., Belzile and Tessier, 1990;Ahmann et al, 1997;Harrington et al, 1998;Cummings et al, 1999;McArthur et al, 2001;Hö hn et al, 2001;Harvey et al, 2002;Horneman et al, 2004;Kent and Fox, 2004;Swartz et al, 2004;van Geen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The exact pH adsorption behavior may be attributed to the acid-base characteristics of aqueous As(V) and As(III), and acid-base characteristics and adsorption affinity of surface functional groups on the solids (Davis and Kent, 1990;Dzombak and Morel, 1990). Competitive or cooperative effects induced by the presence of other adsorbing anions or cations can significantly influence the adsorption and mobility of As(III) and As(V) (Wilkie and Hering, 1996;Darland and Inskeep, 1997;Gräfe et al, 2004;Kent and Fox, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gediz Ilıca ve Balçova jeotermal alanlarında sıcak sular, alüvyon akifer ve yüzeysel sular için en önemli kirletici kaynaklar olarak belirlenmiştir. Kaynak ve kuyu suyu As içerikleri Gediz Ilıca alanında 0.104-0.172 mg/L, Balçova'da ise 0.164-1.420 mg/L arasında bulunmuştur [14].…”
Section: Türkiye'de Arsenik Kirlenmesiunclassified